IMPLEMENTASI PERATURAN DIREKSI PT. PLN (Persero) NOMOR 088-Z.P.DIR/2016 TENTANG PENERTIBAN PEMAKAIAN TENAGA LISTRIK (Studi pada PT. PLN (persero) Unit Layanan Pelanggan (ULP) Lhokseumawe) - Cut Sukmawati; Yussi Hanifa (Negotium: Jurnal Ilmu Administrasi Bisnis, 2021)
The purpose of this study was to determine the implementation of the Regulations of the Board of Directors of PT. PLN (Persero) Regarding Controlling the Use of Electricity. Data collection techniques in this study were to observe, conduct interviews and documentation. The type of this research is to use a qualitative approach. The result of this research is the Implementation of the Regulations of the Board of Directors of PT. PLN (Persero) concerning Control of Electricity Use is carried out through planning, inspection, action and settlement. Obstacles in implementing the Regulation of the Board of Directors of PT. PLN (Persero) regarding Control of Electricity Use is known to be difficult to implement because it can be seen from the planning, even though P2TL has been determined that violations are still carried out, when conducting inspections it often happens that people are not in place so that officers do not continue their duties in inspections, violations are still carried out because people do not receive further action and be resolved according to the criminal law, and at the settlement stage, P2TL is difficult to be resolved routinely because PT. PLN (Persero) Lhokseumawe does not have enough personnel or field teams. It is hoped that the leadership at the Lhokseumawe City District level should pay more attention to the development of the P2TL Program in order to further reduce the level of fraud in the use of electricity. Be more assertive in taking action against any form of fraud from the public in the use of electricity.